Pneumonia after Repair of Esophageal Atresia–Incidence and Main Risk Factors - Nurminen, Paula; Koivusalo, Antti; Hukkinen, Maria; Pakarinen, Mikko (European Journal of Pediatric Surgery, 2019)
Introduction Esophageal atresia (EA) is associated with significant respiratory mortality. We aimed to assess incidence and predictive factors of EA associated pneumonia during the first 5 years of life.Materials and Methods Institutional ethical consent was obtained. Hospital records of patients with EA from 2002 to 2017 were reviewed. Episodes of pneumonia that were diagnosed in university or regional hospitals were included. For instance, respiratory infections other than pneumonia, anastomotic complications, aortopexy, fundoplication, major EA associated diseases, types of EA, and EA anastomosis dilatations were tested as potential risk factors for pneumonia.Results A total of 104 patients (56 males; type A 7, B 3, C 83, D 3, E 6, F 2) was included. Thirty-five (34%) patients had 94 episodes of pneumonia corresponding to median 2 (IQR [interquartile range]: 1–4) and 609 episodes per thousand patient years. Majority of pneumonias occurred before the age of 3 years. The cause of pneumonias could be identified as RS (respiratory syncytial) virus in 15(16%) and aspiration in seven (7.4%) episodes. In univariate analysis, pneumonia was predicted by occurrence and number of nonpneumonia respiratory infections, anastomotic reoperations, fundoplication, and number of EA anastomosis dilatations. In multivariate logistic regression analysis, significant risk factors for pneumonia were occurrence of nonpneumonia respiratory infections and number of anastomotic dilatations.Conclusion Episodes of pneumonia occurred in one-third of patients with EA. After the final repair, the incidence of pneumonia was highest during the first 3 years of life. Patients with other acute respiratory infections and high number of dilatations were at the greatest risk.
Keywords: pneumonia; esophageal atresia; acute respiratory infection